(untitled) (Hoboken, N.J., 2006)
The first book in the series, Iran, gives readers the necessary background to understand important, ongoing developments in the Middle East's most volatile nation. With President Bush's second term inaugural speech signaling a devotion to the spread of democracy in the Middle East, international attention is turning to the White House's policy toward Iran. With entries ranging from Afghanistan and America to Women and Westernization, this balanced briefing examines Iran's current political and cultural climate as the country threatens to become the new focus of America's foreign policy.
Keywords: Iran,Iran; History,Lịch sử